(untitled) (Jurnal Geomine, 2015)
Blasting geometry factors had effect to result blasting rocks volume. In this study aimed to know effect depth of explosive hole to fragmentation. The research method by directly observation on field. In the observational datas taken were depth of explosive hole, pattern of blasting, stuffing explosives each hole. The result showed that there was not insufficient between blasting geometry planning with blasting geometry actual caused over size fragmentation result. Blasting geometry planning should 6,20 cm but in the field/ actual 5,30 cm. Even though, there were different any blasting geometry factors, but littles than dept of explosive hole factor. As the result, concluded that blasting geometry factors had a relations to fragmentation result especially depth of explosive hole.